T cell immunoglobulin and mucin domain-containing protein 3 is highly expressed in patients with acute decompensated heart failure and predicts mid-term prognosis - Meng, Xin; Xia, Guofang; Zhang, Lili; Xu, Congfeng; Chen, Zhong (Frontiers in Cardiovascular Medicine, 2022)
Background and aims: T cell immunoglobulin and mucin domain-containing protein 3 (Tim-3) is mainly expressed by immune cells and plays an immunomodulatory role in cardiovascular disease. However, the prognostic value of Tim-3 in acute decompensated heart failure (ADHF) is unclear. This study aimed to investigate the expression profile of Tim-3 on CD4+ and CD8+ T cells in patients with ADHF and its impact on their prognosis. Methods: In this prospective study, 84 patients who were hospitalized with ADHF and 83 patients without heart failure were enrolled. Main clinical data were collected during patient visits. The Tim-3 expression on CD4+ and CD8+ T cells in peripheral blood samples was assayed by flow cytometry. Long-term prognosis of the patients with ADHF was evaluated by major adverse cardiac and cerebrovascular events (MACCE) over a 12-month follow-up period. Results: We found that the Tim-3 expression on CD4+ T cells (2.08% [1.15%-2.67%] vs. 0.88% [0.56%-1.39%], p < 0.001) and CD8+ T cells (3.81% [2.24%-6.03%] vs. 1.36% [0.76%-3.00%], p < 0.001) in ADHF group were significantly increased vs. the non-ADHF group. Logistic analysis revealed that high levels of Tim-3 expressed on CD4+ and CD8+ T cells were independent risk factors of ADHF (OR: 2.76; 95% CI: 1.34-5.65, p = 0.006; OR: 2.58; 95% CI: 1.26-5.31, p = 0.010, respectively). ROC curve analysis showed that the high level of Tim-3 on CD4+ or CD8+ T cells as a biomarker has predictive performance for ADHF (AUC: 0.75; 95% CI: 0.68-0.83; AUC: 0.78, 95% CI: 0.71-0.85, respectively). During a median follow-up of 12 months, the Cox regression analysis revealed that higher Tim-3 on CD4+ and CD8+ T cells were strongly associated with increased risks of MACCE within 12 months after ADHF (HR: 2.613; 95% CI: 1.11-6.13, p = 0.027; HR: 2.762, 95% CI: 1.15-6.63, p = 0.023; respectively). Conclusion: Our research indicated that the expression level of Tim-3 on CD4+ and CD8+ T cells, elevated in patients with ADHF, was an independent predictor of MACCE within 12 months after ADHF. It suggests a potential immunoregulatory role of Tim-3 signaling system in the mechanism of ADHF.